2020
DOI: 10.1136/gutjnl-2019-318817
|View full text |Cite
|
Sign up to set email alerts
|

MiR130b from Schlafen4+ MDSCs stimulates epithelial proliferation and correlates with preneoplastic changes prior to gastric cancer

Abstract: The myeloid differentiation factor Schlafen4 (Slfn4) marks a subset of myeloid-derived suppressor cells (MDSCs) in the stomach during Helicobacter-induced spasmolytic polypeptide-expressing metaplasia (SPEM).ObjectiveTo identify the gene products expressed by Slfn4+-MDSCs and to determine how they promote SPEM.DesignWe performed transcriptome analyses for both coding genes (mRNA by RNA-Seq) and non-coding genes (microRNAs using NanoString nCounter) using flow-sorted SLFN4+ and SLFN4– cells from Helicobacter-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…One of the biggest challenges in developing miRNA-based therapeutics is to identify the best miRNA candidates or miRNA targets for each disease type. Although several GC-implicated miRNAs have been identified [ 6 , 19 ], the functions and mechanisms of miRNAs in GC progression and metastasis are still poorly understood. Thus, identification of novel miRNA candidates involved in this disease and understanding of their targets and downstream pathways are needed to develop effective miRNA-based therapeutics for gastric carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…One of the biggest challenges in developing miRNA-based therapeutics is to identify the best miRNA candidates or miRNA targets for each disease type. Although several GC-implicated miRNAs have been identified [ 6 , 19 ], the functions and mechanisms of miRNAs in GC progression and metastasis are still poorly understood. Thus, identification of novel miRNA candidates involved in this disease and understanding of their targets and downstream pathways are needed to develop effective miRNA-based therapeutics for gastric carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Recent characterization of the infiltrating PMN-MDSCs in response to Helicobacter infection in the stomach showed that these immunosuppressive cells have a unique signature. These Arg1+/NOS2+ PMN-MDSC population express the Schlafen (SLFN) family of proteins, a transcriptional target of GLI1, and the endogenous small, non-coding RNA, MiR130b [ 29 , 30 ]. SLFN12L + myeloid cells express VEGF, IL-1β and TNF-α, which are known factors associated with MDSC regulation, an immunosuppressive cell of relevance to immunotherapy-resistant gastric cancer [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These SLFN-expressing MDSCs secrete factors including microRNAs, which can be detected in the peripheral blood as a biomarker and promote epithelial cell growth. This sustained immune dysregulation creates a microenvironment capable of supporting GC development[ 46 ].…”
Section: Mdscs In Gi Malignanciesmentioning
confidence: 99%